2018
DOI: 10.1159/000486698
|View full text |Cite
|
Sign up to set email alerts
|

Growth Trajectory in Children with Type 1 Diabetes Mellitus: The Impact of Insulin Treatment and Metabolic Control

Abstract: Background: Linear growth was reported to be negatively affected by type 1 diabetes mellitus (T1DM), in relation to disease duration and poor metabolic control. It is unclear whether a subtle growth failure still persists despite the optimization of therapy. Our aim was to analyse pubertal growth, adult height, and metabolic profile in a cohort of children with T1DM undergoing intensive insulin treatment by multiple daily injections or continuous subcutaneous insulin infusion (CSII). Methods: One-hundred and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 24 publications
1
25
0
3
Order By: Relevance
“…Abnormalities in growth and puberty in children with type 1 diabetes mellitus (T1D) have been prevalent complications in children with poor metabolic control; concerns about deficiencies in final height or the timing of pubertal development remain …”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities in growth and puberty in children with type 1 diabetes mellitus (T1D) have been prevalent complications in children with poor metabolic control; concerns about deficiencies in final height or the timing of pubertal development remain …”
Section: Introductionmentioning
confidence: 99%
“…Though modern therapies based on MDI or CSII with new insulin analogues ensure more physiological insulin supplementation than previous therapies, some anomalies of the GH/IGF-1 axis are still detectable due to persistent hepatic hypo-insulinization. However, modern intensive insulin regimens, leading to improved metabolic control, are able to ensure a normal adult height in line with patients’ target parameters [22,59]. Therefore, currently, the choice of the most appropriate therapeutic regimen to achieve a good insulin level and the best metabolic control for each patient, together with the regular measurement of growth parameters, remains the most important available tool for a pediatric diabetologist.…”
Section: Discussionmentioning
confidence: 99%
“…Height at the diagnosis of T1DM in children is a debated topic in the literature. Many studies have reported that children at the onset of T1DM were taller than their healthy peers [27,46,47,48,49,50,51,52,53,54,55,56,57,58,59], while other authors have not confirmed these data [29,30,60,61,62] (Table 1). A possible reason for the differences between these results could be the secular trend in growth (i.e., the fact that puberty is starting earlier for boys and girls now than it did a hundred years ago) and an inadequate choice of controls [63].…”
Section: Height At Diagnosis Of Type 1 Diabetes Mellitus (T1dm) Anmentioning
confidence: 99%
See 2 more Smart Citations